Pengaruh Permainan Jigsaw Puzzle terhadap Kemampuan Pemecahan Masalah Anak Usia 5-6 Tahun di RA Ikhlasul Amal Medan - Fitria Nur Afni Siregar; Ahmad Syukri Sitorus (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
The purpose of this study was to examine the effect of Jigsaw Puzzle games on the problem-solving abilities of children aged up to 6 years at Raudhatul Athfal Ikhlasul Amal Medan. This study involved 12 students from group B, using quantitative methodology and a pre-experimental one-group pretest-posttest design. Data were collected through observations using a rating scale instrument and statistically analyzed using the Shapiro-Wilk normality test and paired t-test using SPSS 26. The main findings indicated a significant effect on children's problem-solving abilities after the Jigsaw Puzzle game intervention. The low average pretest score increased in the posttest, supported by a very small t-test significance value (0.000), indicating a statistically significant difference. It was concluded that Jigsaw Puzzle games are an effective medium for stimulating early childhood problem-solving abilities, training logical thinking, spatial reasoning, patience, and motivation, and can be recommended for developing an Early Childhood Education curriculum.